Clades of huge phages from across Earth’s ecosystems - Al-Shayeb, Basem; Sachdeva, Rohan; Chen, Lin-Xing; Ward, Fred; Munk, Patrick; Devoto, Audra; Castelle, Cindy J.; Olm, Matthew R.; Bouma-Gregson, Keith; Amano, Yuki; He, Christine; Méheust, Raphaël; et al. (Nature (London), 2020)
Bacteriophages typically have small genomes 1 and depend on their bacterial hosts for replication 2 . Here we sequenced DNA from diverse ecosystems and found hundreds of phage genomes with lengths of more than 200 kilobases (kb), including a genome of 735 kb, which is—to our knowledge—the largest phage genome to be described to date. Thirty-five genomes were manually curated to completion (circular and no gaps). Expanded genetic repertoires include diverse and previously undescribed CRISPR–Cas systems, transfer RNAs (tRNAs), tRNA synthetases, tRNA-modification enzymes, translation-initiation and elongation factors, and ribosomal proteins. The CRISPR–Cas systems of phages have the capacity to silence host transcription factors and translational genes, potentially as part of a larger interaction network that intercepts translation to redirect biosynthesis to phage-encoded functions. In addition, some phages may repurpose bacterial CRISPR–Cas systems to eliminate competing phages. We phylogenetically define the major clades of huge phages from human and other animal microbiomes, as well as from oceans, lakes, sediments, soils and the built environment. We conclude that the large gene inventories of huge phages reflect a conserved biological strategy, and that the phages are distributed across a broad bacterial host range and across Earth’s ecosystems. Genomic analyses of major clades of huge phages sampled from across Earth’s ecosystems show that they have diverse genetic inventories, including a variety of CRISPR–Cas systems and translation-relevant genes.